Wiener polynomial and Wiener index of conical graphs - Ayache, Ahmed; Alameri, Abdu; Ghallab, Abdullatif; Modabish, Abdelhafid (Sylwan, 2020)
Topological indices have important role in theoretical chemistry. Among the Wiener index has been used more considerably than any other topological indices in chemical literature. In this study, we introduce a new graphs called conical graphs G(m, n) that generalizes the classic wheel graphs.The Wiener polynomial of G(m, n) has been computed. We present explicit formulae for the Wiener index of G(m, n) by considering the cases ? n 4 ? ? m and ? n 4 ? > m.